TAX BURDEN OF DOMESTIC ENTERPRISES IN CONDITIONS OF MARTIAL LAW: METHODOLOGICAL ASPECT - MATVIYCHUK, Lesia; OLIINYK, Larysa (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article investigates scientific approaches to determining the level of tax burden of the enterprise, proposes an author's approach based on the determined tax burden on all taxes actually paid by the enterprise, takes into account the level of SSC payment, as well as the level of payment discipline and accounts payable. with a budget. It is determined that insufficient attention to the level of tax burden of the enterprise and determining its impact on key parameters of financial and economic activities deprives businesses of competitive advantages in an unstable market environment. Reducing the tax burden on business will increase the working capital of enterprises, the formation of additional resources to overcome the challenges that arise now, ie will allow businesses to work and you yourself to rebuild the economy. In the course of the research the changes of the tax legislation are analyzed and their influence on the level of tax burden of enterprises in the conditions of martial law is investigated. It is determined that along with the liberalization of tax legislation and reduction of tax pressure at the state level, it is expedient for business entities to optimize and regulate the tax burden by developing their own effective tax policy.The tax policy of enterprises should include: the choice of taxation system (general taxation system or simplified taxation system); determination of tax benefits and the possibility of their application at the enterprise; financial and economic transformation and diversification and changes in the tax burden of the enterprise (management of inventory balances; outsourcing of major and ancillary business processes; optimization of revenue and transfer parts of income to other legal entities or individuals - entrepreneurs who have less tax pressure; non-taxable resources such as repayable financial assistance, replenishment of authorized capital, leasing, profit generation in companies registered in jurisdictions with a more favorable tax system than Ukraine, in international transactions, provided the owner builds a chain of controlled transactions, etc.), as a whole for the enterprise (planning the amount of taxes, fees and mandatory payments in accordance with applicable regulations, rates and approved methods; modeling of tax bases for each individual tax or fee paid by the enterprise); development of a tax calendar; determining and evaluating the effectiveness of the developed tax policy and taxation system of the enterprise.
Keywords: tax burden; enterprise; tax policy of the enterprise; evaluation methodology; tax policy of the state